Comparative Study of Translation Effects in Low-Resource Languages Based on Pivot Language Method - Qi, Jinyue (Journal of Educational Research and Policies, 2024)
This study aims to compare and analyze the translation effects of low-resource languages in Asia based on the Pivot Language method. By selecting five different low-resource languages in Asia (Urdu, Burmese, Kyrgyz, Kazakh, and Tajik), this study explores the translation effect of using a pivot language (usually English) to build a bridge between the source language and the target language, and compares it with direct translation. The study uses two translation modes, Pivot Translation Technique and Pivot Prompting, to compare the quality differences between translation through a pivot language and translation directly from the source language to the target language. By calculating translation quality evaluation indicators such as Comet and BLEU, this study evaluates the performance of the two translation modes in different languagesand analyzes whether adding a pivot language can effectively improve translation quality, especially in terms of grammatical accuracy, semantic transmission, and fluency of expression. The results show that the pivot language method significantly improves the accuracy and fluency of translation in low-resource language translation, especially in the translation of long and difficult sentences, and the pivot language translation has higher quality than direct translation. This discovery provides a new direction for machine translation research in low-resource languages and is of great significance to the country's cross-language communication and cultural cooperation.